Estimating thermal stability of phosphated and phosphated sulfated mesoporous zirconia - Van, Phong Pham; Hong Nguyen, Khanh Dieu (Vietnam Journal of Science and Technology, 2016)
Mesoporous phosphated zirconia (m-PZ) and mesoporous phosphated sulfated zirconia (m-PSZ) were synthesized through condensation methods using Zr3(PO4)4 and Zr(SO4)2 as precursors respectively. The precursors, solvents with suitable molar or mass ratios were mixed at 100oC for 48 hours to obtain the mesoporous channels. An oxophosphate process was used to synthesize the m-PSZ material for improving its thermal stability. Some techniques was used to characterize the materials such as SAXRD, TG-DTA and TEM.